Design of Detecting and Sorting Equipment for Egg Quality Based on Arduino Uno Microcontroller - Ahmad Baiquni Fariz Azka; Muhammad Nur Kholis; Shoffin Nahwa Utama (Agroindustrial Technology Journal, 2020)
n the industrial sector, current Artificial Intelligence (AI) is widely used as an effort to optimize the production process. At this time the industrial era entered into the industrial era 4.0, wheresthe industry is required to develop techniques in the process of using automation in order to compete with other competitors. One of themis thechicken egg industry. This study aims to create an arduino uno-based detection instrument automation to facilitate the process of detecting and sorting egg quality, and to evaluate the system functionality in detecting and sorting eggs.The types ofeggs detected were purebred eggs. Prototype Testing Arduino uno-based egg quality detection and sorting tools use the functional test method for each component or commonly called the Black Box method, testing the entire tool system and testing the measurement of egg thickness and thickness. The test results obtained that all components of the tool function properly and work in accordance with its function. This can be seen from the workings of the components in receiving commands from running program. The second trial that from the was the reliability testing tool bydetecting and sorting egg quality by testing the level of accuracy of the tool in detecting egg quality and the accuracy of the tool in placing eggs into good or bad categories. In testing the reliability of the tool, the results show that the accuracy of the tool in detecting eggs is in the figure at 98% while in the egg sorting process is at 100%. The third test wastesting the thickness and thinness of the egg to determine the quality of the egg, the results showedthe thickness and thinness of the egg to be one indicator of egg quality. Good quality eggs has charachtersisticd such asthick, whilebad eggs, indicaterunny. The results showed the accuracy of the tools included in both categories so that they can run the program well. Eventuallythis tool can be used in the process of detecting and sorting egg quality in industry or business units to facilitate the process of detecting and sorting egg quality